An initial study of disclosures related to broad-based black economic empowerment in the integrated reports of South African mining companies - Nkhi, Naledi (My University, 2016)
This research takes a snap-shot look at Broad-based Black Economic Empowerment disclosures in the integrated reports of South African mining companies listed on the Johannesburg Stock Exchange. A Broad-based Black Economic Empowerment disclosure checklist, based on relevant literature, was developed by the researcher in order to analyse the basic or inherent features, characteristics or qualities - and the extent of the disclosures in the 2014/2015 integrated reports. The results reveal that listed mining companies include an adequate coverage of Broad-based Black Economic Empowerment-related disclosures in their integrated reports. The sufficient frequency of the disclosures is clouded by a lack of integration between the relevant themes. The reports also noted a considerable amount of repetition of the themes and a scarcity of disclosures linking the risks of mining operations to Broad-based Black Economic Empowerment.
A research report submitted In partial fulfillment of the degree Master of Commerce in Accounting University of the Witwatersrand School of Accountancy 2016
Keywords: Corporation reports; Corporate governance--South Africa; Corporation reports--South Africa